Image quality control for linear transducers with various frequencies by using an ATS-550 phantom - Jung, James J.; Choi, Jae-Ho; Jung, Jae Hong (Journal of the Korean Physical Society, 2017)
The purpose of this study is to evaluate the image quality for linear transducers on the basis of a quality control (QC) protocol using the ATS-550 phantom (ATS, Laboratories, Bridgeport, CT, USA). To evaluate the image QC, we used two linear transducers L9 and ML6-15 and performed eight examinations, which included qualitative and quantitative analyses by three observers. The qualitative analyses mostly showed no difference between the two transducers at various frequencies. However, in the functional resolution, the distinguishing ability of anechoic holes ranged between 13 and 15 MHz in the ML6-15 transducer. For quantitative analyses, the vertical and the horizontal measurements were in the range of 2.00 - 2.02 cm, and the focus rate (%) in the focal zone was greater than 75% (range: L9, 85.22 - 89.78%; ML6 - 15, 81.72 - 88.21%) in most the transducers. For sensitivity, the L9 transducer values (mean ± SD) for all frequencies were 6.02 ± 0.01 cm and the ML6-15 transducer values (mean ± SD) for frequencies 9, 11, 13, and 15 MHz were 6.03 ± 0.02, 6.01 ± 0.01, 5.03 ± 0.05, and 4.03 ± 0.05 cm, respectively. For the signal-to-noise ratio of the gray scale and dynamic image, the mean values of the L9 transducer for frequencies 5, 5.5, 6, 7, and 9 MHz were 2.50 ± 1.44, 2.64 ± 1.52, 2.47 ± 1.43, 2.13 ± 1.35, and 2.03 ± 1.24, respectively. The mean values of the ML6-15 transducer for frequencies 9, 11, 13, and 15 MHz were 4.02 ± 1.67, 3.56 ± 1.60, 2.18 ± 1.14, and 2.48 ± 1.01, respectively. For the contrast-to-noise ratio of the gray scale and dynamic image, mean values of the L9 transducer and the ML6-15 transducer were in the ranges of 0.82 - 0.98 and 0.97 - 1.05, respectively. The image quality of the linear transducer depends on the frequency whereas the diagnostic values depend on the transducer and the frequency selected. As yet, the QC of linear transducers has no standard protocol. The results of this study can be used to understand the characteristics of linear transducers and perform QC tests. Consequently, periodic QC testing of linear transducers can provide improved image quality and increased diagnostic values.